Cerebral neurovascular embryology, anatomic variations, and congenital brain arteriovenous lesions - Jesse M. Klostranec; Timo Krings (2022)
Cerebral neurovascular development is a complex and coordinated process driven by the changing spatial and temporal metabolic demands of the developing brain. Familiarity with the process is helpful in understanding neurovascular anatomic variants and congenital arteriovenous shunting lesions encountered in endovascular neuroradiological practice. Herein, the processes of vasculogenesis and angiogenesis are reviewed, followed by examination of the morphogenesis of the cerebral arterial and venous systems. Common arterial anatomic variants are reviewed with an emphasis on their development. Finally, endothelial genetic mutations affecting angiogenesis are examined to consider their probable role in the development of three types of congenital brain arteriovenous fistulas: vein of Galen malformations, pial arteriovenous fistulas, and dural sinus malformations.